First Amendment Institutions - Novit-Evans, Bette (A journal of church and state, 2014)
First Amendment Institutions offers a persuasive critique and reformulation of First Amendment doctrine, but readers of this journal should be aware that only one chapter focuses on church/state jurisprudence. Horwitz, who is Gordon Rosen Professor of Law at the University of Alabama School of Law, advocates one essential idea: First Amendment jurisprudence should be attentive to the institutions that form “infrastructure of free expression” (p. 3). As a pluralist, he understands human beings as social creatures, many of whose most important activities take place within institutions. Society is not a single system but a variety of subsystems, each operating according to its own norms and interacting only imperfectly with others.